2004
DOI: 10.1007/s00424-003-1214-9
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial outer membrane is not a major diffusion barrier for ADP in mouse heart skinned fibre bundles

Abstract: The response of mitochondrial oxygen consumption to ADP in saponin-skinned cardiac fibre bundles has an apparent Km an order of magnitude higher than that in isolated mitochondria. Here we report that incubating skinned cardiac fibre bundles from wild-type mice or double-knockout mice lacking both cytosolic and mitochondrial creatine kinase (CK) with CK and creatine or with yeast hexokinase and glucose as extramitochondrial ADP-producing systems decreases the apparent Km of the bundles for ADP severalfold. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The finding of an adaptive increase in respiratory V max in M-CK -⁄and MiM-CK -⁄gastrocnemius mitochondria is in line with the results of previous studies on muscle homogenate that reported an increase of mitochondrial protein in these genotypes [10,[13][14][15]. Also, the results of polarographic measurements of respiratory V max (but not K ADP 50 ; see [16]) in permeabilized M-CK -⁄gastrocnemius fibres, which can be compared to our results in a straightforward manner, are similar [11,17]. Our present investigations did not provide insight into the exact sites of V max up-regulation in M-CK -⁄and MiM-CK -⁄phenotypes in terms of activities of individual components of the respiratory chain.…”
Section: Fast-twitch Glycolytic Skeletal Musclesupporting
confidence: 91%
“…The finding of an adaptive increase in respiratory V max in M-CK -⁄and MiM-CK -⁄gastrocnemius mitochondria is in line with the results of previous studies on muscle homogenate that reported an increase of mitochondrial protein in these genotypes [10,[13][14][15]. Also, the results of polarographic measurements of respiratory V max (but not K ADP 50 ; see [16]) in permeabilized M-CK -⁄gastrocnemius fibres, which can be compared to our results in a straightforward manner, are similar [11,17]. Our present investigations did not provide insight into the exact sites of V max up-regulation in M-CK -⁄and MiM-CK -⁄phenotypes in terms of activities of individual components of the respiratory chain.…”
Section: Fast-twitch Glycolytic Skeletal Musclesupporting
confidence: 91%
“…The MOM conductance for ADP and ATP is of major importance for theories about the phosphocreatine shuttle and regulation of mitochondrial ATP synthesis, but is apparently not well known, as demonstrated by the considerable differences in its value between various models and experimental results (4,24,25,32,41). The other parameters in the present model were either measured independently in the same experimental model in the same laboratory (CK activities, mitochondrial aerobic capacity, metabolite concentrations), or represent well established literature values for kinetic constants of enzyme processes (MM-CK, Mi-CK, oxidative phosphorylation).…”
Section: Resultsmentioning
confidence: 99%
“…Much higher, sometimes triple-digit micromolar, estimates of KmADP [70] are reported as a simple MM parameter, although proteolytic treatment to remove putative linkages between VDAC and the cytoskeleton reduces KmADP into the double-digit micromolar range, as does the addition of 20 mM creatine [66, 71, 72]. However, diffusional issues related not to mitochondria but rather to the experimental conditions may be confounding the interpretations of this experimental approach [73]. As a technical note it is worth pointing out that permeabilized fiber preparations maintain very high bound CK activity [74], which is largely accounted for by a myofibrillar CK activity that is about 24 times higher than the CK in the mitochondrial intermembrane space [75, 76].…”
Section: Discussionmentioning
confidence: 99%